1994
DOI: 10.1007/bf00009592
|View full text |Cite
|
Sign up to set email alerts
|

A re-evaluation of the phylogeny of Parelaphostrongylus Boev & Schulz, 1950 (Nematoda: Protostrongylidae)

Abstract: The phylogeny of the genus Parelaphostrongylus was reconstructed using Elaphostrongylus rangiferi as an outgroup. Parelaphostrongylus is monophyletic and divided into two clades, one containing the meningeal worm, P. tenuis of white-tailed deer, and the other consisting of two muscle-inhabiting forms, P. andersoni and P. odocoilei of white-tailed and mule deer, respectively. Differences in biological features, including tissue migration route and prepatent period, are mapped onto the cladogram and discussed. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The geographically broad range now demonstrated for this previously undescribed protostrongylid suggests that it may have existed in caribou in refugia in eastern Beringia or south of the Laurentide-Cordillera during the Pleistocene (e.g., Flagstad and Røed 2003); additionally this may suggest affinities to a Holarctic-Palearctic fauna during the Pleistocene (Hoberg 2005). In as much as we have shown that the unknown may not be an elaphostrongyline, any history that has been defined for Parelaphostrongylus (e.g., Platt 1984;Carreno and Lankester 1994) may not be revealing with respect to this protostrongylid.…”
Section: Host and Geographic Rangementioning
confidence: 62%
See 1 more Smart Citation
“…The geographically broad range now demonstrated for this previously undescribed protostrongylid suggests that it may have existed in caribou in refugia in eastern Beringia or south of the Laurentide-Cordillera during the Pleistocene (e.g., Flagstad and Røed 2003); additionally this may suggest affinities to a Holarctic-Palearctic fauna during the Pleistocene (Hoberg 2005). In as much as we have shown that the unknown may not be an elaphostrongyline, any history that has been defined for Parelaphostrongylus (e.g., Platt 1984;Carreno and Lankester 1994) may not be revealing with respect to this protostrongylid.…”
Section: Host and Geographic Rangementioning
confidence: 62%
“…Although elaphostrongylines are characteristic in caribou and reindeer, no other protostrongylids are known (Boev 1975;Lankester 2001), and in North America, P. andersoni appears to be a colonizer from white-tailed deer (Carreno and Lankester 1994). The geographically broad range now demonstrated for this previously undescribed protostrongylid suggests that it may have existed in caribou in refugia in eastern Beringia or south of the Laurentide-Cordillera during the Pleistocene (e.g., Flagstad and Røed 2003); additionally this may suggest affinities to a Holarctic-Palearctic fauna during the Pleistocene (Hoberg 2005).…”
Section: Host and Geographic Rangementioning
confidence: 99%
“…A general pattern of disjunct distributions between eastern Asia and eastern North America has been reported for a variety of animal and plant taxa (Carreno & Lankester 1994;Nordlander et al 1996;Wang et al 2003;Nie et al 2006). This pattern was known from plants before Linnaean times (Xiang et al 1998;Wen 1999) and has also been reported in wasps (Nordlander et al 1996) and fishes (Hardman 2005).…”
Section: Introductionmentioning
confidence: 72%
“…A general pattern of disjunct distributions between eastern Asia and eastern North America has been reported for a variety of animal and plant taxa (Carreno & Lankester 1994; Nordlander et al. 1996; Wang et al.…”
Section: Introductionmentioning
confidence: 85%
“…Historical biogeography of these host-parasite assemblages and development of associations of these parasites with cervids and caprines is complex and can be initially considered in the context of phylogenetic inference among the protostrongylids and species of Varestrongylus. An ancestral association with cervids has been proposed for Varestrongylus [ 13 ], which is supported by the host-associations of the Elaphostrongylinae, the sister group of Varestrongylinae [ 2 ], also primarily parasites of cervids [ 1 , 3 , 4 , 78 ]. Concurrently, this supports a primary association of V. eleguneniensis with caribou and secondary host switching to muskoxen and moose in zones of relatively recent to very recent contact, proposed by Hoberg et al [ 13 ].…”
Section: Discussionmentioning
confidence: 99%